Diagnostic Parameters of CT FESS Protocol in Diagnosis of Fungal Sinusitis with Histopathology as a Gold Standard - Baig, Mah Rukh; Sarfraz, Saulat; Ijaz, Mubashir; Aman, Shazia; Naseer, Madiha (Indus Journal of Bioscience Research, 2025)
Background: Fungal sinusitis is an increasingly recognized cause of chronic rhinosinusitis, and early diagnosis is essential for appropriate management. Computed tomography (CT) of the paranasal sinuses is widely used for preoperative evaluation; however, its diagnostic accuracy compared with histopathology remains variable. Objectives: To determine the diagnostic accuracy of CT FESS findings in detecting fungal sinusitis using histopathology as the gold standard and to assess its performance after stratification by age, gender, and duration of complaints. Study Design & Setting: This cross-sectional validation study was conducted at the Departments of ENT and Radiology at Shaikh Zayed Hospital, Lahore 2 April 2025 to 1 July 2025. Methodology: A total of 99 patients clinically suspected of having fungal sinusitis were included. All patients underwent CT scan of the paranasal sinuses followed by Functional Endoscopic Sinus Surgery (FESS). Specimens obtained during surgery were sent for histopathological examination. CT findings were compared with histopathology results. Data were stratified by age, gender, and duration of complaints, and post-stratification chi-square tests were applied using SPSS version 26. Results: Out of 99 patients, CT FESS was positive in 70 (70.7%) cases, while histopathology confirmed fungal sinusitis in 65 (65.7%) cases. CT FESS demonstrated high diagnostic performance with a statistically significant association with histopathology results (p < 0.001). Stratified analysis showed that the diagnostic accuracy of CT FESS remained significant across different age groups, genders, and durations of symptoms. Conclusion: CT FESS is a reliable and accurate diagnostic tool for the detection of fungal sinusitis, showing strong agreement with histopathology across various patient subgroups. Its use can aid in early diagnosis and appropriate surgical planning.